Analyses of Ca2+ dynamics using a ubiquitin‐10 promoter‐driven Yellow Cameleon 3.6 indicator reveal reliable transgene expression and differences in cytoplasmic Ca2+ responses in Arabidopsis and rice (Oryza sativa) roots. Issue 2 (5th January 2015) - Behera, Smrutisanjita; Wang, Nili; Zhang, Chunxia; Schmitz‐Thom, Ina; Strohkamp, Sarah; Schültke, Stefanie; Hashimoto, Kenji; Xiong, Lizhong; Kudla, Jörg
Summary: Ca 2+ signatures are central to developmental processes and adaptive responses in plants. However, high‐resolution studies of Ca 2+ dynamics using genetically encoded Ca 2+ indicators (GECIs) such as Yellow Cameleon (YC) proteins have so far not been conducted in important model crops such as rice ( Oryza sativa ). We conducted a comparative study of 35S and ubiquitin‐10 (UBQ10) promoter functionality in Arabidopsis thaliana and O .  sativa plants expressing the Ca 2+ indicator Yellow Cameleon 3.6 (YC3.6) under control of the UBQ10 or 35S promoter. Ca 2+ signatures in roots of both species were analyzed during exposure to hyperpolarization/depolarization cycles or in response to application of the amino acid glutamate. We found a superior performance of the UBQ10 promoter with regard to expression pattern, levels and expression stabilities in both species. We observed remarkable differences between the two species in the spatiotemporal parameters of the observed Ca 2+ signatures. Rice appeared in general to respond with a lower maximal signal amplitude but greatly increased signal duration when compared with Arabidopsis. Our results identify important advantages to using the UBQ10 promoter in Arabidopsis and rice and in T‐DNA mutant backgrounds. Moreover, the observed differences in Ca 2+ signaling in the two species underscore the need for comparative studies to achieve a comprehensive understanding of Ca 2+ signaling in plants.